Problems and Mysteries of the Many Languages of Thought. Issue 12 (20th December 2022) - Mandelbaum, Eric; Dunham, Yarrow; Feiman, Roman; Firestone, Chaz; Green, E. J.; Harris, Daniel; Kibbe, Melissa M.; Kurdi, Benedek; Mylopoulos, Myrto; Shepherd, Joshua; Wellwood, Alexis; Porot, Nicolas; et al.
Abstract: "What is the structure of thought?" is as central a question as any in cognitive science. A classic answer to this question has appealed to a Language of Thought (LoT). We point to emerging research from disparate branches of the field that supports the LoT hypothesis, but also uncovers diversity in LoTs across cognitive systems, stages of development, and species. Our letter formulates open research questions for cognitive science concerning the varieties of rules and representations that underwrite various LoT‐based systems and how these variations can help researchers taxonomize cognitive systems.